2011
DOI: 10.1097/ajp.0b013e3181eef903
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of the BDI-II Among People With Chronic Pain Originating From Musculoskeletal Disorders

Abstract: The importance of assessing somatic symptoms of depression in pain patients and of thoroughly examining the underlying perceived cause of symptoms, regardless of the dimension, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Different from the original version, which intended to measure negative cognitions of depression, the BDI-II does not reflect any particular theory of depression. The English version of BDI-II has been translated and validated in 17 languages so far, and it is used among countries in Europe, the Middle East, Asia, and Latin America (29-32). …”
Section: Introductionmentioning
confidence: 99%
“…Different from the original version, which intended to measure negative cognitions of depression, the BDI-II does not reflect any particular theory of depression. The English version of BDI-II has been translated and validated in 17 languages so far, and it is used among countries in Europe, the Middle East, Asia, and Latin America (29-32). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some studies have suggested that the structure of BDI-II can be best described as three-dimensional, distributing the cognitive-affective dimension into two distinct factors. 17,20,41,56,66,98,122,136 Further analyses revealed that the BDI-II presents reasonable factorial invariance when assessing the severity of depressive symptoms; this covariance structure is equivalent across gender and ethnicity in American college students 58 and across gender in Taiwanese college students and adolescents. 60,61 Sophisticated alternative structural analysis of the BDI-II was strengthened by two investigative breakthroughs: the hierarchical model and the bifactor model.…”
Section: Content and Construct Validitymentioning
confidence: 99%
“…Several studies in adult pain samples have used factor analysis of similar measures of depression to examine the specific influence of somatic symptoms on total and subscale scores. 8,14,33,36,49 Overall, these studies have concluded that caution is needed when using traditional self-report depression measures to assess depression in the context of chronic pain due to a high level of endorsement of somatic symptoms. It is unclear whether these somatic symptoms truly reflect depression or are more closely linked to the chronic pain experience itself.…”
mentioning
confidence: 99%